Effects of genotype and acclimation on honeybee thermal responses - Rylance, Elizabeth, author; Naug, Dhruba, advisor; Hoke, Kim, committee member; Hufbauer, Ruth, committee member (Colorado State University. Libraries, 2025)
As global temperatures rise, animals are increasingly exposed to changing thermal environments that challenge their physiological and behavioral performance. Genetic variation and phenotypic plasticity are two key factors that influence how organisms respond to such environmental change. Understanding the capacity and limitations of these responses is essential for predicting species resilience under climate change. In this thesis, I investigate how thermal responses are shaped by 1) short-term thermal acclimation and 2) genotypic differences at a key metabolic enzyme locus in honeybees, a species of high ecological and agricultural importance. In the first chapter, I assessed the capacity for short-term acclimation to mitigate the effects of thermal stress. Bees were acclimated for 48 hours to either a cool (25°C) or warm (35°C) temperature and subsequently tested at both acclimation and non-acclimation temperatures. Metabolic rate showed evidence of compensatory acclimation, with warm-acclimated bees maintaining stable performance at high temperature. In contrast, activity and learning performance declined following heat exposure, with no evidence of a beneficial acclimation response. These results suggest that energetically demanding traits such as cognition and locomotion may have a more limited capacity for acclimation and higher vulnerability to sustained heat stress. In the second chapter, I examined how genetic variation in a key metabolic enzyme, malate dehydrogenase (MDH-1), influences thermal performance. Bees representing homozygous Slow (SS), homozygous Fast (FF), and heterozygous (SF) genotypes were assayed across four temperatures and three traits: metabolic rate, locomotor activity, and learning ability. Metabolic rate exhibited a strong genotype-by-temperature interaction; Fast bees consistently had the highest rates, Slow bees the lowest, and heterozygous bees had flexible, intermediate responses. Activity levels varied with both genotype and temperature, while learning performance was influenced by genotype but not temperature. Heterozygotes outperformed both homozygous types in the learning assay, suggesting a potential heterozygote advantage. These results highlight how functional diversity in a key metabolic enzyme can shape trait performance across thermal gradients, with broader implications for colony-level function and honeybee breeding practices. Together, these chapters show that both genetic variation and phenotypic plasticity influence how bees respond to thermal variation, but their effects vary across different performance traits. Genetic variation may support flexible trait expression across environments, whereas short-term acclimation alone may be insufficient to maintain performance in key behavioral traits under thermal stress. These findings emphasize the importance of integrative, trait-based approaches to evaluating thermal responses and have implications for understanding pollinator performance and adaptation in a warming world.
Keywords: animal behavior; plasticity; honeybees; acclimation